Pre- and post anthesis factors affecting apple fruit growth and the development of a model to predict size at harvest - Bergh, O.(Oloff) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D. Agric.) -- University of Stellenbosch, 1984.